Long-Term Outcomes of Intentional Head Trauma in Infants: A Comprehensive Follow-Up of Medical, Developmental, Psychological, and Legal Perspectives - Göksel Vatansever; Ezgi Özalp Akın; Pınar Bingöl Kızıltunç; Didem Behice Öztop; Kezban Karabağ; Seda Topçu; Betül Ulukol (Medicina)
Background and Objectives: This study aimed to determine the initial clinical characteristics of children diagnosed with intentional head trauma (IHT) to obtain information about the long-term developmental, psychological, and psychosocial status of these children, to detect delayed sequelae, and to find out information about their judicial processes. Materials and Methods: Fourteen children who were followed up with the diagnosis of IHT in the Ankara Child Protection Unit between 2010 and 2021 were included in the study. These cases were evaluated in terms of physical, developmental, psychological, and visual findings. A complete physical examination was performed on the patients and their anthropometric measurements were taken. Anterior and posterior segment evaluations and visual field examinations were conducted in the visual assessment. The Expanded Guide for Monitoring Child Development and Vineland Adaptive Behavior Scale Third Edition was used in the developmental assessment. A psychiatric evaluation was performed using the Ankara Developmental Screening Inventory, Crowell observation, Affective Disorders and Schizophrenia Form, and Wechsler Intelligence Scale for Children. Results: Of the patients diagnosed with IHT, 71.4% were male and the mean age was 8.39 ± 5.86 (1.27–22.30; IQR: 3.55–11.96) months. In the long-term follow-up, cerebral palsy was detected in three of the children, epilepsy in one, optic atrophy and deviation due to this in one, and deviation due to brain trauma in one. Motor delay was detected in 50.0% of the patients, language delay in 37.5%, cognitive delay in 37.5%, and attention deficit and hyperactivity disorder in 25%. It was observed that the people who caused the injuries of two patients were punished. Conclusions: Children diagnosed with IHT should be monitored with transdisciplinary methods in terms of physical and mental health throughout childhood, starting from the first intervention. Awareness of IHT diagnosis should be increased with training in social service approaches and judicial authorities providing services for child neglect and abuse.